MANAGEMENT AND OUTCOME OF ATOPIC DERMATITIS IN PRIMARY HEALTH CARE IN LOW INCOME COUNTRIES : A SYSTEMATIC REVIEW - Yulianto, Ronald; Aristika Gunawan, Ellen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Atopic dermatitis is a chronic inflammatory skin disorder that is complicated and recurring. It usually first appears in early childhood and might persist throughout maturity.Aims : This systematic review is to review the management and outcome of atopic dermatitis in primary health care in low income countries.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 539 articles, whereas the results of our search on SCIENCE DIRECT brought up 9.462 articles, our search on SAGEPUB brought up 1.264 articles. The results of the search conducted for the last year of 2014 yielded a total 425 articles for PubMed, 5.474 articles for SCIENCE DIRECT and 613 articles for SAGEPUB. In the end, we compiled a total of 5 papers, 3 of which came from PubMed, 1 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included five research that met the criteria.Conclusion: In summary, atopic dermatitis is still a major global public health problem, especially for women and young children as well as in high-income nations. It is important to recognize the profound effects on patients, their families, and economies as well as the financial ramifications.